2008
DOI: 10.1021/jf801133h
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Phlorotannins Isolated from Ishige okamurae in Free Radical Mediated Oxidative Systems

Abstract: Three phlorotannins, including phloroglucinol, diphlorethohydroxycarmalol, and 6,6'-bieckol, were isolated from Ishige okamurae by column chromatography. The structures of the phlorotannins were determined on the basis of spectroscopic analysis, including NMR and mass spectrometry (MS) techniques. Antioxidant effects of phlorotannins were measured by direct free radical scavenging activities using the electron spin resonance spectrometry (ESR) technique and cellular systems in vitro. The results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(62 citation statements)
references
References 45 publications
1
58
0
Order By: Relevance
“…30) EC phlorotannin contains such phenolic secondary metabolites as eckol, 6,6 0 -bieckol, dieckol, phlorofucofuroeckol, and triphlorethol-A. 23,24) It has been reported that phlorotannins have such biological properties as antioxidative, 31) anti-inflammatory, 32) antibacterial, 33) antiallergic, 34) and -glucosidase inhibitory 35) effects. To investigate whether the marine polyphenol, phlorotannin, had the same depressive effect on CNS as terrestrial polyphenols, we evaluated the anticonvulsive and sleep-inducing effects of PTRF fractionated from ECEE.…”
Section: Discussionmentioning
confidence: 99%
“…30) EC phlorotannin contains such phenolic secondary metabolites as eckol, 6,6 0 -bieckol, dieckol, phlorofucofuroeckol, and triphlorethol-A. 23,24) It has been reported that phlorotannins have such biological properties as antioxidative, 31) anti-inflammatory, 32) antibacterial, 33) antiallergic, 34) and -glucosidase inhibitory 35) effects. To investigate whether the marine polyphenol, phlorotannin, had the same depressive effect on CNS as terrestrial polyphenols, we evaluated the anticonvulsive and sleep-inducing effects of PTRF fractionated from ECEE.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity of seaweed polyphenols have been reported by many researchers [3][4][5][6]. However, the evaluation of the effects exerted by algal polyphenols gives several problems when moving from in vitro experimental systems to the complexity of in vivo system.…”
Section: Introductionmentioning
confidence: 99%
“…Their sensory characteristics would be suitable as an additive to coffee. In addition, phlorotannins have various biological activities, such as antioxidative (Zou et al, 2008), anti-inflammatory , antibacterial , and antiallergic (Sugiura et al, 2006) effects. Therefore, HP-PRT may be a good additive for the preparation of coffee products without an arousal effect.…”
Section: Resultsmentioning
confidence: 99%